Does Performance Information Affect Job Seekers in Selecting Private Providers in Voucher-Based ALMP Programs? - Christer Gerdes (Institute for the Study of Labor (IZA), 2015)
One of the services provided at the Swedish Public Employment Services is job coaching. Since 2012, that service has been organized according to a voucher-based choice system. In 2013, a performance indicator of job coaching providers was made available at an online website. This study examines to what extent such information affected job coaches' ability to attract participants, as well as how the use of provider ratings varied across different groups of participants. The results indicate that the performance indicator strengthened the positive link between "quality" of services and the number of new participants that signed up with a provider. At the same time, there is evidence showing that more vulnerable groups, such as the less educated and those born outside Europe, do not use the rating values to the same extent as others. It appears that there is a tradeoff as to efficiency and inequality with respect to services that are contracted to private companies in a system based on consumer choice.
Keywords: H41; J64; J68; J78; 330; public sector; private providers; ALMP; rating; efficiency; equality